Motives for Takeovers: An Empirical Investigation - Berkovitch, Elazar; Narayanan, M. P. (Journal of Financial and Quantitative Analysis, 1993)
Three major motives have been suggested for takeovers: synergy, agency, and hubris. Existing empirical evidence is unable to clearly distinguish among these motives probably due to the simultaneous existence of all three in any sample of takeovers. This paper suggests a way of distinguishing among these competing hypotheses by looking at the correlation between target and total gains. It is argued that this correlation should be positive if synergy is the motive, negative if agency is the motive, and zero if hubris is the motive. The empirical results show that synergy is the primary motive in takeovers with positive total gains even though the evidence is consistent with the simultaneous existence of hubris in this sample. It is also found that agency is the primary motive in takeovers with negative total gains.